Kepemimpinan dalam Masyarakat Islam di Indonesia - Syamsudin RS (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2015)
This paper describes the reality of Muslims in Indonesia showed the phenomenon of diversity, both in religious understanding and in menifestasinya on religious social movements. This diversity is in line with the pluralism of Indonesian society itself, on the basis of ethnicity, language and religion. In some cases, this phenomenon is an opportunity and challenge for Muslims in Indonesia to be able to realize the ideals of the ideal leadership in sociologically and theologically.